(untitled) (Journal of Ideas in Health, 2024)
Background: Drug use often leads to a range of health risks, social complications, and involvement in criminal behavior. This study aims to investigate adolescents’ understanding, opinions, and perspectives on substance abuse. Methods: Between October and December 2023, a cross-sectional study was undertaken in Diyala Province, Iraq. High school students were sampled using a multistage sampling technique. Bivariate analysis utilized independent sample t-tests and one-way analysis of variance (ANOVA). Additionally, a multivariable linear regression analysis was performed to predict factors associated with knowledge, attitudes, and perceptions. All statistical analyses were carried out using SPSS version 16. Results: The study encompassed 365 students, with a mean age (SD) of 17.5 (+ 8.2), predominantly male (57.3%). Overall accuracy rates for knowledge, attitude, and perception stood at 87.1%, 86.7%, and 88.7%, respectively. Approximately 5.2% of the sample reported cannabis (hashish) use. Regression analysis revealed significant associations between higher knowledge scores and male gender (p=0.002, 95% CI:0.341, 0.729), urban residency (p<0.0001, 95% CI:1.165, 4.524), and monthly income > US400 (p >0.0001, 95% CI:0.907, 1573). Attitudes toward drug abuse prevention were influenced by male gender and highly educated parental backgrounds (p<0.001, 95% CI:1.412, 5.223; p=0.002, 95% CI: 2.160, 4.881; p=0.007, 95% CI:1.810, 5.690). Perception scores were significantly associated with male gender (p=0.001, 95% CI: 0.430, 0.691), students from smaller families (p=0.013, 95% CI:2.201, 5.003), and those in the sixth class (p=0.021, 95% CI:1.423, 4.202). Conclusion: While adolescents demonstrate a solid understanding of societal norms and consequences associated with substance abuse, there may still be areas where perceptions can be refined and aligned more closely with the realities of drug abuse.